PODCAST SEBAGAI SENJATA RAHASIA DALAM PENGAJARAN KETERAMPILAN MENYIMAK BAHASA ARAB : SOLUSI KREATIF BAGI GENERASI DIGITAL - Fatahilla Fatahilla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Listening skill is a fundamental pillar in Arabic language acquisition, yet it often receives insufficient attention in instructional practice. On the other hand, the emergence of the digital-native generation calls for innovation in learning media that aligns with contemporary learning styles. This article aims to examine the potential of podcasting as an innovative tool in teaching Arabic listening skills. This research adopts a qualitative approach through a literature study, utilizing a range of scientific sources such as journals, academic books, and recent studies. The findings reveal that podcasts offer high flexibility, provide authentic language input, and can enhance learners’ motivation and autonomy. However, the integration of podcasts also faces several challenges, including infrastructure limitations, teacher readiness, and the variation of available Arabic-language content. Supported by language learning theories such as Comprehensible Input, Dual Coding, and Cognitive Load, podcasting is deemed feasible to be systematically integrated into Arabic listening curriculum. This article offers strategic recommendations and conceptual contributions for the development of adaptive and effective Arabic language learning models based on educational technology.